Office XP brief edition : (McGraw-Hill, 2003)
Office XP: Brief edition, one of the instructional tools that complements Peter Nortons introduction to computers, covers the basic features of Office XP. Glencoe and Peter Norton have teamed up to provide this tutorial and its ancillaries to help you become a knowledgeable, empowered end user. After you complete this tutorial, you will be able to create and modify documents, explore the World Wide Web, and produce Web pages.